2015
DOI: 10.1002/cctc.201500101
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Fe–Ni Alloy on a Ceria Support as a Noble‐Metal‐Free Catalyst for Hydrogen Production from Chemical Hydrogen Storage Materials

Abstract: Bimetallic FeNi nanoparticles supported on CeO2 was proven to be effective for hydrogen production from ammonia–borane (NH3–BH3) as a noble‐metal‐free catalyst. Impregnation of iron and nickel ions with the CeO2 surface followed by in situ reduction with NaBH4 prior to catalytic dehydrogenation of AB produced highly dispersed and partially oxidized amorphous FeNi NPs stabilized by strong interaction with the CeO2 support by NiOCe and FeOCe bonding. Investigation of the influence of the Fe/Ni ratio revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 53 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…3d transition metal-based catalysts comprised of Ni were also explored for the hydrolysis of AB with good activity, where Ni-Fe and Ni-Cu combinations were found to be the most active. [174][175][176][177] Xu and coworkers reported magnetically recyclable Fe 1Àx Ni x nano-alloy catalysts which exhibited Pt-like high catalytic activity. 175 Kim et al prepared bimetallic NiCu nanorods (NRs) incorporated into carbon nanofibers (NFs) that showed superior catalytic activity toward H 2 release from AB as well as excellent recyclability and chemical stability.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…3d transition metal-based catalysts comprised of Ni were also explored for the hydrolysis of AB with good activity, where Ni-Fe and Ni-Cu combinations were found to be the most active. [174][175][176][177] Xu and coworkers reported magnetically recyclable Fe 1Àx Ni x nano-alloy catalysts which exhibited Pt-like high catalytic activity. 175 Kim et al prepared bimetallic NiCu nanorods (NRs) incorporated into carbon nanofibers (NFs) that showed superior catalytic activity toward H 2 release from AB as well as excellent recyclability and chemical stability.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, CeO 2 supported bimetallic Ni-Fe NPs were reported as efficient noble-metal-free catalysts for AB hydrolysis. 174 The catalyst is comprised of highly disperse and partially oxidized amorphous Ni-Fe NPs stabilized by strong interactions with the CeO 2 support via Ni-O-Ce and Fe-O-Ce bonding. The influence of Fe/Ni ratio on catalytic activity revealed a volcano-shaped relationship with a maximum at Fe/Ni = 1 : 1 (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…However, the concerns over the practical use of these high cost metals have motivated the research for the development of low cost catalyst systems in the hydrolytic dehydrogenation of AB. In this context, the recent studies have revealed that heterogeneous catalysts of low-cost 3d metals such as Fe [25][26][27], Co [28][29][30][31][32][33][34][35][36][37], Ni [38][39][40][41][42][43][44] and Cu [45][46][47][48] can catalyze the hydrolytic dehydrogenation of AB. Unfortunately, most of these low-cost catalytic systems suffer from low activity and reusability performance.…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising approaches towards clean and safe hydrogen‐storage materials is the utilization of hydrides, borohydrides, ammoniates, and ammonia borane (AB). Considering the hydrolysis of AB, the reaction rate is almost negligible at room temperature in the absence of catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[24,25] Numerous efforts have been made to establish as afe and efficient storage system for hydrogen. [26,27] One of the promising approaches towards clean and safe hydrogen-storage materials is the utilization of hydrides, [28] borohydrides, [29,30] ammoniates, [31,32] and ammonia borane [33][34] (AB). Consideringt he hydrolysis of AB, the reactionr ate is almostn egligible at room temperature in the absence of cata- lyst.…”
Section: Catalytic Dehydrogenation Activity Of Ag Nps Supported On Timentioning
confidence: 99%